2019
DOI: 10.3961/jpmph.18.270
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Stillbirth Among Pregnant Women in Nepal

Abstract: Objectives: Stillbirth is a common adverse pregnancy outcome that represents a distressing and traumatic event for women and their partners. The aim of this study was to identify factors associated with stillbirth in ever-pregnant women in Nepal. Methods: This study utilized the individual women’s dataset from the Nepal Demographic and Health Survey, conducted in 2016. The dependent variable of interest was whether women had at least 1 stillbirth during their lifetime. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 23 publications
4
11
0
Order By: Relevance
“…It was supported by previous studies conducted in Uganda [ 44 ], and Nepal [ 45 ]. Wealthier mothers are more conscious about maternal health, the importance of a balanced diet, and the need for ANC visits, and maybe more likely to be aware of unhealthy behaviors [ 46 ]. Women in poor households are less likely to use maternal health care services such as family planning service, ANC visit, and health facility delivery though these services are free of charge they are unable to cover the indirect costs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was supported by previous studies conducted in Uganda [ 44 ], and Nepal [ 45 ]. Wealthier mothers are more conscious about maternal health, the importance of a balanced diet, and the need for ANC visits, and maybe more likely to be aware of unhealthy behaviors [ 46 ]. Women in poor households are less likely to use maternal health care services such as family planning service, ANC visit, and health facility delivery though these services are free of charge they are unable to cover the indirect costs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is also higher than the report of another Nigerian study conducted among women that delivered at the primary and secondary health facilities, but lower than the report of a similar study in Nepal. 17,18 The differences here, may be due to differences in antenatal services at the health facilities studied and the availability and accessibility of health care in these localities.…”
Section: Discussionmentioning
confidence: 94%
“…17 Other studies however, contradicts the findings of our study reporting that still birth was higher among less educated women. 18,23,25,26 Other studies have also shown that stillbirth was higher in women with no formal education with the rate of stillbirth decreasing with increasing educational status. 27,28 These may be attributed to unemployment and lack of prenatal care during pregnancy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nepal has had some success in reducing maternal and under-five mortality over the last few decades. However, as of 2016, maternal death rates, neonatal death rates, and stillbirth rates remained high (258 deaths per 100,000 live births, 21 deaths per 1000 live births, 18 deaths per 1000 births) [16, 17].…”
Section: Introductionmentioning
confidence: 99%